(untitled) (Revista de Estudos da Linguagem, 2015)
Abstract: This article reports on the phenomenon of omission in the subtitles of the TV series Heroes from an Audiovisual Translation/Systemic Functional Linguistics (AVT/SFL) standpoint. In order to test and expand on the methodological framework put forward by Kovačič (1998), the present study investigates the meanings translated out of the subtitles in terms of experiential, interpersonal, and textual realizations. The analyses reveal a different construal considering the spoken dialogues and their subtitled counterparts for the linguistic construal of the subtitles may sometimes prevent the spectator from having access to certain meanings from the narrative being recreated or construe a different message than the one being realized by the characters in the series. Thus, the different construal the subtitles present impacts on the flux of events of the episode in the same way that the goings-on were impacted by the omissions found in the data herein investigated. Keywords: Subtitling; Omission; Systemic Functional Linguistics; Metafuncional Meanings. Resumo: Este artigo aborda o fenômeno da omissão de significados metafuncionais nas legendas do seriado de TV Heroes, apoiando-se no arcabouço teórico da Linguística Sistêmico-Funcional, especialmente na dimensão metafuncional, e no arcabouço metodológico proposto por Kovačič (1998). Com base nisso, o artigo tem por objetivo investigar os significados ideacionais, interpessoais e textuais omitidos nas legendas em português brasileiro, o que impede que o espectador brasileiro tenha acesso a significados realizados nos diálogos entre os personagens da série, impactando também diretamente na representação do fluxo de eventos presentes no episódio em estudo. Palavras-chave: legendagem; omissão; linguística sistêmico-funcional; significados metafuncionais.